2016
DOI: 10.1038/sigtrans.2016.10
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting cancer cell hallmark features through nuclear export inhibition

Abstract: Treating cancer through inhibition of nuclear export is one of the best examples of basic research translation into clinical application. Nuclear export factor chromosomal region maintenance 1 (CRM1; Xpo1 and exportin-1) controls cellular localization and function of numerous proteins that are critical for the development of many cancer hallmarks. The diverse actions of CRM1 are likely to explain the broad ranging anti-cancer potency of CRM1 inhibitors observed in pre-clinical studies and/or clinical trials (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 174 publications
(244 reference statements)
2
132
0
Order By: Relevance
“…CRM1 has been observed to play a role in inflammatory diseases, viral infections, wound healing, and most notably in cancer [10]. The overexpression of CRM1 seen in many different types of cancers is correlated with increased metastasis, histological grade, tumor size, and decreased survival [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…CRM1 has been observed to play a role in inflammatory diseases, viral infections, wound healing, and most notably in cancer [10]. The overexpression of CRM1 seen in many different types of cancers is correlated with increased metastasis, histological grade, tumor size, and decreased survival [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, CRM1 inhibition might be an interesting therapeutic option in NUP214related leukemia, similarly as described for several cancer models, including other forms of leukemia 23,24,29,54,55 . This notion is further supported by a recent study that showed successful disease remission for an AML patient with NUP214 driven leukemia who was treated with KPT-330 as single agent 56,57 .…”
Section: Discussionmentioning
confidence: 60%
“…In fact, both fusion proteins can bind CRM1 and its co-factor, the small GTPase Ran, and inhibit the nuclear export of NES-containing proteins and RNPs 17,18 . Targeted CRM1 inhibition by small molecule antagonists has become an appealing anti-cancer strategy, for both solid and hematologic malignancies [20][21][22][23][24] . Leptomycin B (LMB), a fungal metabolite from Streptomyces spp, was the first identified small molecule inhibitor specifically targeting CRM1 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the modulation of protein function by specific signal transduction inhibitors is one of the therapeutic tools for CML [25][26][27]. In this study, we examined the effects of a small molecule, TH-39, which potentially targets the Hec1/Nek2 interaction, and our results indicated that TH-39 exhibited antitumor efficacy in K562 cells via G0/G1 cell cycle arrest and apoptosis induction.…”
Section: Discussionmentioning
confidence: 95%